The scaling technology in nuclear reactor thermal hydraulic. (October 2021) - Wang, L.S.; Yan, B.H.
Highlights: Scaling play a key role in nuclear reactor safety analysis and integral test. The origin of scaling distortion is explained. The technologies of scaling in nuclear reactor thermal hydraulic are overviewed. Valuable conclusions and suggestions for future work are proposed. Abstract: Scaling is an important issue in nuclear reactor safety analysis. Due to the safety relevance and cost, it is a big challenge for the scientists to design and construct experimental facilities capable of simulating the performance of nuclear reactor systems. Several approaches have been developed to address the scaling issue, including non-dimensional analysis of conservative equations, derivation and application of scaling factors, etc. In this work, the key areas and approaches for scaling technology in nuclear reactor thermal hydraulic are systematically analyzed and summarized. Some valuable conclusions and suggestions for future work are proposed.